KUAT TEKAN BETON POROUS DENGAN SUBTITUSI AGREGAT KASAR LIMBAH PECAHAN GENTENG DENGAN PERSENTASE 0% 15% 45% 75% - Rivan Bima Risqiantok; Dewi Sulistiorini; Afif Shulhan; Angga Darmawan (Department of Civil Engineering, Faculty of Engineer, Universitas Sarjanawiyata Tamansiswa, 2024)
Concrete is a mixture of Portland cement or other hydraulic cements, fine aggregates, coarse aggregates, and water, with or without the use of additives that form a solid mass. Porous concrete, known as pervious concrete, is a type of concrete that is porous or hollow in its structure, allowing the possibility of fluid flow through the gaps present in the concrete. Tile fragments are the remnants of the tile production process or tiles that are defective during manufacturing and cannot be reused. Currently, the utilization of tile waste is still ineffective, necessitating research to enhance the use of tile fragments, particularly as coarse aggregates in concrete mixtures. This study employs an experimental method in the laboratory. The test specimens consist of porous concrete with tile fragment substitution percentages of 0%, 15%, 45%, and 75%, totaling 12 specimens. Each variation of tile fragment percentage includes 3 test specimens in the form of concrete cylinders with a diameter of 15 cm and a height of 30 cm. Tests for concrete porosity and compressive strength are conducted at 28 days of concrete age.